Analysis of the impact and effectiveness of official multilateral financing on socio-economic development: a case study of the Kyrgyz Republic (1992-2017) - Roman V. Manshin; Goran A. Sumkoski (RUDN Journal of Economics)
This study analyzes the impact of officially multilateral foreign funds in the Kyrgyz Republic on its economy, on broader socio-economic development. It identifies key strengths, obstacles, weaknesses, lessons from different periods official multilateral financing and the key features of the public investment system with foreign loans. The analysis shows the positive impact of public investment on socio-economic development, although this positive effect is significantly reduced due to the debt trap, high servicing costs, a large share of lost effects from loans owed to both creditors and countries from operational failures as well as economic and financial mistakes. A sensitivity analysis is conducted showing the size and impact of possible additional effects on the country’s economic development and growth, budgets and debt levels that could be achieved through more efficient implementation of public investment processes, improved project selection, preparation, and optimization of investment project implementation, as well as better utilization foreign financial funding.